"Click" dendrimer-Pd nanoparticle assemblies as enzyme mimics: catalytic o-phenylenediamine oxidation and application in colorimetric H2O2 detection. Issue 13 (27th May 2021) - Liu, Yue; Lopes, Renata Pereira; Lüdtke, Tanja; Di Silvio, Desire; Moya, Sergio; Hamon, Jean-René; Astruc, Didier
Abstract : "Click" dendrimer-Pd NPs as peroxidase enzyme mimics of H2 O2 sensing using o -phenylenediamine oxidation by H2 O2 to 2, 3-diaminophenazine. Abstract : Dendrimers have already been successfully used in nanoparticle (NP) catalysis for many years, particularly for Pd NP protection towards carbon–carbon coupling reactions. In this paper, assemblies between Pd nanoparticles and two generations of "click" dendrimers, with 27 (dendrimer-1 ) and 81 (dendrimer-2 ) triethylene glycol (TEG) termini, respectively, are examined for catalytic peroxidase-like oxidative activity. This catalysis is investigated with o -phenylenediamine (OPD) and H2 O2 as the substrates in water, displaying different colours. The dendritic effect is negative upon increasing generation, i.e., dendrimer 1 -Pd nanoparticles show the best results, providing values with a V max of 1.49 × 10 −9 M s −1 and K m of 3.02 mM as obtained with the Michaelis–Menten model. The detection limit is 0.5 μM of H2 O2 detection with dendrimer-1 -PdNPs, and both dendrimer-Pd nanocatalysts exhibit excellent robustness of catalytic activity, with a water-dispersive state being stable for at least 2 months, thus showing promise as a mimic for peroxidase catalysts.